Analisis Penyelenggaraan Pelayanan Publik yang Inovatif di Masa Era Revolusi 4.0 - Madubun, Hadijah; Selly, Rina Nuraini (Public Policy, 2023)
The purpose of this research is to analyze the implementation of innovative Era 4.0 in Ambon City and the variables that influence it. This study uses a qualitative approach by utilizing descriptive data. Observations, interviews, documents, and archives are used to obtain data. They were subjected to a qualitative descriptive analysis. The findings show that the application of digital/electronic government aspects in information services has not been carried out optimally. The SIMANTAP, SIMANJA, and Smart City applications have been implemented well but not yet optimal at the Ambon City Government Information Communication Service. This is evidenced by the large number of applicants who continue to provide services offline, especially by visiting service offices. For this reason, it is necessary to improve the quality of human resources, facilities and infrastructure, as well as provide socialization to the public regarding the existence and use of applications.